A Study Of Prevalence Of Obesity In Adult Punjabi Population - Goyal, Pooja; Sachar, R K; Soni, R K (Indian Journal of Community Health, 2006)
Introduction : Obesity has reached epidemic proportions globally with more than 1 billion overweight, Atleast 300 million of them are clinically obese and is a major contributor to the global burden of chronic disease and disability (1). Long considered a buy product of modern life in rich, developed contries, obesity is spreading to developing contries as well. Two critical factors that have influenced this explosion are changes in dietary patterns and levels of physical activity. The latest list of morbidity associated with obesity includes about forty diseases. Though, prevalence of co-morbidities of obesity is quite high among adults in India yet there are relatively less reliable and representative data available. Hence, this study was carried out. Material & Methods : It was a community based, cross sectional study conducted in field practice areas at Rural Health Centre (RHC), Pohir and Urban Health Centre (UHC), Kirti Nagar attached to the department of Community Medicine, DMC & Hospital Ludhiana. Field practice area of RHC is composed of 10 villages serving a total population of 20,450. The Urban health Centre covers ten colonies having a total populaation of 20.645.